(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Staphylococcus aureus is a Gram-positive cocci involved in food spoilage. It is one of opportunistic pathogens causes serious surgical wound infections, lifethreatening blood stream and bone infections, or pneumonia, osteomyelitis, meningitis and sepsis. It is frequently found in skin causing serious infections such as pimples, boils, and abscesses. According to world health organization (WHO), consumption of any food or water contaminated with microbes or its toxic nature leading to foodborne illnesses posing to be a major healthcare problem throughout the world. The contagious nature of these diseases makes itimperative for early diagnosis of the microbes to preventthe spread of epidemics. Conventional standard diagnostic methods have limitations such as difficulty in sample preparation, time consuming, and poor sensitivity. The inappropriate use of antimicrobial drugs increases the prevalence of biofilm forming drug-resistant methicillin-resistance Staphylococcus aureus (MRSA) is one of great challenging factors in the control of S. aureus in the food processing environments and disease conditions. Hence, robust field deployable diagnostic modalities arein urgent need to identify, and efficient technology to combat the problems of food-spoilage and infection caused by S. aureus. This thesis aims to screen various food-samples from different areas of Mysuru to understand the prevalence of food-borne pathogens, developing robust identification method, nanotechnology approach to control its infection, and developing novel food wrap to stop food-spoilage caused by S. aureus suitable for developing countries. To realize these objectives, we screened different food samples and isolated 500 food-borne pathogens. Among them, methicillin-resistant S. aureus (MRSA) showed highest prevalence in the region of Mysuru. The MALDIBiotyper evolved as robust and sensitive method by identifying MRSA in 2 min compared to conventional methods. Also, PCR-SSCP evolved as novel sensitive nucleic acid based method to identify food-borne pathogens by discriminating at species level. Both MALDI-Biotyper and PCR-SSCP recognized for point-of-care and unsophisticated laboratories applications respectively, from the present study.